SOS & biofeedback at SRK Wira - Munira, Abdul Razak (Pusat Bahasa Moden dan Sains Kemanusiaan, 2010)
2 - 3 June 2010. This programme was executed for a research purpose entitled “The development of Study Orientation Skills (SOS) kit and biofeedback protocol to improve academic performance of primary schools students.” It had successfully created a module named The Ghani Module Format (Modul Format Ghani) for the Primary School Achievement Examination (UPSR).